Technostress of Chilean Teachers in the Context of the Covid-19 Pandemic and Teleworking - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This article shows the levels of technostress in primary and secondary education teachers in Chile, in the context of educational telework that Chile has adopted in connection with the health crisis by COVID-19. The information has been collected with the use of the RED-TIC scale, previously used in this country, whose validity and reliability of the instrument has been treated, for this case, with confirmatory factorial analysis (CFA) with a national coverage sample of 3006 teachers. The results show that 11% of teachers reveal techno anxiety and 7.2%, techno fatigue. Combining both manifestations, we find that 6.8% of teachers are techno stressed. Finally, fatigue and anxiety factors are higher for female teachers. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.